2017
DOI: 10.1063/1.5003420
|View full text |Cite
|
Sign up to set email alerts
|

Effective suppression of parametric instabilities with decoupled broadband lasers in plasma

Abstract: A theoretical analysis for the stimulated Raman scattering (SRS) instability driven by two laser beams with certain frequency difference is presented. It is found that strong coupling and enhanced SRS take place only when the unstable regions for each beam are overlapped in the wavenumber space. Hence a threshold of the beam frequency difference for their decoupling is found as a function of their intensity and plasma density. Based upon this, a strategy to suppress the SRS instability with decoupled broadband… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 34 publications
0
41
0
1
Order By: Relevance
“…Early work showed that the single-beam homoge-neous temporal growth rate (γ 0 ) could be reduced by a factor of γ 0 /δω when δω ≫ γ 0 [22,27,28]. The homogeneous growth rate for TPD can easily be ∼ 1% of the laser frequency for ICF conditions, which suggests δω/ω 0 ≫ 1% is required to have a significant impact on TPD [29,30]. However, in an inhomogeneous plasma, these results are only directly applicable to instabilities that saturate convectively (i.e., undergo finite spatial amplification) because the convective gain is directly related to the linear growth rate.…”
mentioning
confidence: 99%
“…Early work showed that the single-beam homoge-neous temporal growth rate (γ 0 ) could be reduced by a factor of γ 0 /δω when δω ≫ γ 0 [22,27,28]. The homogeneous growth rate for TPD can easily be ∼ 1% of the laser frequency for ICF conditions, which suggests δω/ω 0 ≫ 1% is required to have a significant impact on TPD [29,30]. However, in an inhomogeneous plasma, these results are only directly applicable to instabilities that saturate convectively (i.e., undergo finite spatial amplification) because the convective gain is directly related to the linear growth rate.…”
mentioning
confidence: 99%
“…The pump laser required here is achievable in many laser facilities worldwide [25]. This scheme paves a way to experimentally demonstrate some theoretical predictions, such as the suppression of laser plasma instabilities via multi-frequency broad bandwidth laser in ICF [11,12].…”
Section: Introductionmentioning
confidence: 87%
“…Usually they have narrow bandwidths. High-power intense laser, especially that with broad bandwidth, have many advantages for applications, such as incoherent laser acceleration [6][7][8], THz radiation generation [9], parametric instability suppression [10][11][12], shock ignition and related astrophysics study [3,4,13]. Normal optical components are not suitable to modulate intense laser pulse due to their low damage threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Let us consider the bandwidth effects of backscattering light at the near-quarter-critical density, where the mismatch of wave numbers becomes much weak. The width of the instability region in the plasma wave vector ∆k is proved to be a critical factor for the modes coupling [26]. The dispersion for SRS in homogeneous plasma is given by [1] where…”
Section: Theoretical Analysis Of the Absolute Instability Modes Via Rmentioning
confidence: 99%